CIRCRNA CIRCEHBP1 REGULATES THE MATURATION OF MIR-129 TO INCREASE THE CHEMORESISTANCE OF CANCER CELLS TO ADRIAMYCIN IN ACUTE MYELOID LEUKAEMIA - Hong Li; Kehong Bi; Saran Feng; Yan Wang; Chuansheng Zhu (Mediterranean Journal of Hematology and Infectious Diseases)
Background: MiR-129 promotes the chemosensitivity of cancer cells in many cancers. The role of miR-129 in acute myeloid leukaemia (AML) is unclear. We predicted that premature miR-129 might interact with circEHBP1, a well-characterized oncogene in bladder cancer. We then analyzed the interaction between circEHBP1 and miR-129 in AML.